Tindak Tutur Komisif dalam Dorama Alice in Borderland Season 1 Karya Haro Aso - Agnes, Monica; Suciaty, Prisyanti (Lembaga Yasin AlSys, 2024)
This research aims to examine in more depth the function and form of commissive speech act sentences in the drama